Pharmacological properties of bergapten: mechanistic and therapeutic aspects - Quetglas-Llabrés, Maria Magdalena (2022)
Bergapten (BP) or 5-methoxypsoralen (5-MOP) is a furocoumarin compound mainly found in bergamot essential oil but also in other citrus essential oils and grapefruit juice. This compound presents antibacterial, anti-inflammatory, hypolipemic, and anticancer effects and is successfully used as a photosensitizing agent. The present review focuses on the research evidence related to the therapeutic properties of bergapten collected in recent years. Many preclinical and in vitro studies have been evidenced the therapeutic action of BP; however, few clinical trials have been carried out to evaluate its efficacy. These clinical trials with BP are mainly focused on patients suffering from skin disorders such as psoriasis or vitiligo. In these trials, the administration of BP (oral or topical) combined with UV irradiation induces relevant lesion clearance rates. In addition, beneficial effects of bergamot extract were also observed in patients with altered serum lipid profiles and in people with nonalcoholic fatty liver. On the contrary, there are no clinical trials that investigate the possible effects on cancer. Although the bioavailability of BP is lower than that of its 8-methoxypsoralen (8-MOP) isomer, it has fewer side effects allowing higher concentrations to be administered. In conclusion, although the use of BP has therapeutic applications on skin disorders as a sensitizing agent and as components of bergamot extract as hypolipemic therapy, more trials are necessary to define the doses and treatment guidelines and its usefulness against other pathologies such as cancer or bacterial infections.